Relationships Analysis of Revenue, Price Perceptions, Product Quality and Services to Consumer Purchasing Decisions Beverages in Banda Aceh - Muhammad Hajarul Aswad (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
This study aims to determine the relationship between income, price perception, product quality and service on consumer purchasing decisions of beverages in Banda Aceh. This study uses a survey method. The sampling technique used is accidental sampling with a sample of 100 people. Data collection techniques using a questionnaire. The data analysis technique used chi-square analysis. The results showed that income, product quality and service had a relationship with consumer purchasing decisions for beverages, while price perceptions had no relationship with consumer buying decisions for beverages. This is because income, product and service quality have χ2 count χ2 table and significant at 0.00 0.05 (significant effect) while price perception has χ2 count χ2 table and significant at 0.055 0.05 (no effect and not significant).